2015
DOI: 10.1021/acs.jpca.5b00572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Pressure on the Kinetics of the Oxygen Reduction Reaction

Abstract: Fundamental understanding of the oxygen reduction reaction in aqueous medium at temperatures above 100 °C is lacking due to the practical limitations related to the harsh experimental conditions. In this work, the challenge to suppress water from boiling was overcome by conducting the electrochemical investigation under pressurized conditions. A striking improvement in the kinetics of the electrocatalytic reduction of O2 by about 150 fold relative to room temperature and pressure was recorded under an O2 press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 110 publications
1
43
0
Order By: Relevance
“…3 Ω, and iR correction was 5 done following published procedures. [69][70][71] Unless otherwise stated, the scan rate was 10 mV s -1 .…”
Section: Methodsmentioning
confidence: 99%
“…3 Ω, and iR correction was 5 done following published procedures. [69][70][71] Unless otherwise stated, the scan rate was 10 mV s -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of ORR has been extensively investigated in the past. 15,16,25,[17][18][19][20][21][22][23][24] It is known that platinum nanoparticles can catalyze ORR. [26][27][28] Although nanoparticles with smaller size, around 1 nm, cannot efficiently catalyze ORR due to poisoning, 29 it has been shown that Pt subnano clusters catalyze ORR at even higher rate than nanoparticles.…”
Section: Table Of Content Graphicsmentioning
confidence: 99%
“…The formation of nanoparticles and the reduction of blue silver ion using the extract of the plant was determined by the color change of the mixture to a yellow-brown (Figure 1). 19,20…”
Section: Synthesis Of Silver Nanoparticles Using T Brevifolia Extractmentioning
confidence: 99%